[ICF, digitalisation and clinical care pathways in rehabilitation medicine: a possible integration from the goal-planning and the rehabilitation programme design to the evaluation of clinical outcomes] (Giornale Italiano di Medicina del Lavoro ed Ergonomia, 2025)
In the light of the growing complexity featuring the contemporary world, a future challenge is represented by the maintenance of the humanization of healthcare, along with the necessity of a highspecificity personalized treatment, in a growing emergency of lack of resources. Furthermore, the ongoing digital revolution spreading in every productive sector involves the health-care system as well, playing a crucial role for the goals of the specialized care-related prevention-treatment-rehabilitation approach of the Rehabilitation Medicine. However, the digitalization of clinical data is not to be considered as a mere tout-court necessity, but it deserves to be planned and carried out with consistent awareness: the digital transformation calls for a theoretical paradigm which, together with a shared language, will be able to embrace its multilevel complexity, taking into account the patient needs, the clinical care pathways and the administrative requests. In the present work the potentialities of the WHO ICF model (International Classification of Functioning, Disability and Health) will be described. In particular, will be discussed the role of the ICF in representing the keystone able to connect the ICD-9-CM classification, the clinical care pathways, the individualized rehabilitation project and program and their digital implementation. Hence, each step of the process that led the implementation of the biopsychosocial model in the ICF Maugeri workflows will be presented, as well as the critical issues related to the digitalisation process and the strengths in safeguarding the patients’ wellbeing.